2017
DOI: 10.1021/acs.chemmater.7b02133
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Chemical Transformations at the Brønsted Acid Site upon Water-Induced Deprotonation in a Zeolite Pore

Abstract: The structural changes induced by reversible formation of Brønsted acidic sites and hydronium ions with water in a zeolite with MFI structure are reported as a function of temperature using a combination of physicochemical methods and theory. In the presence of an ample concentration of water, the protons are present as hydrated hydronium ions (H 3 O + (H 2 O) n ) that are ion-paired to the zeolite. Loss of water molecules hydrating the hydronium ions leads to an unstable free hydronium ion that dissociates to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
106
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(128 citation statements)
references
References 94 publications
13
106
0
Order By: Relevance
“…The above mechanistic hypotheses are supported by numerous reports in the literature suggesting that zeolites at 348–423 K retain one to three water molecules at their acid site, and thus may still contain H 7 O 3 + trimers, H 5 O 2 + dimers, and H 3 O + cations up to 423 K [30,31]. Alberti and colleagues reported a neutron diffraction study indicating that residual H 2 O participates in the H/D-exchange at the level of the acid sites [32].…”
Section: Discussionsupporting
confidence: 58%
“…The above mechanistic hypotheses are supported by numerous reports in the literature suggesting that zeolites at 348–423 K retain one to three water molecules at their acid site, and thus may still contain H 7 O 3 + trimers, H 5 O 2 + dimers, and H 3 O + cations up to 423 K [30,31]. Alberti and colleagues reported a neutron diffraction study indicating that residual H 2 O participates in the H/D-exchange at the level of the acid sites [32].…”
Section: Discussionsupporting
confidence: 58%
“…Such a complex water network is due primarily to the topology of the zeolite void space, which comprises small cages connected by narrow (8-ring) windows. Additionally, the water is protonated to a degree estimated at ~99% 33 , due to the equilibrium between Brønsted proton adsorption at the Al–O–Si group, and solvation in the water 3436 . At 300 K, we find this equilibrium to lie on the side of solvation (See Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen bonding between a single water molecule and an isolated BAS is not strong enough to form a H 3 O + hydronium, but these can be stabilized upon more extensive solvation to form hydronium clusters H 3 O + (H 2 O) 2 . It was also shown that the ion‐paired hydronium clusters can expel water molecules to form zeolite BAS upon the decrease of the temperature . In addition, the solvation effect and proton transport efficiency can be induced by dispersion interactions as exemplified by the combined NMR and DFT study of trimethylphosphine oxide (TMPO) adsorption in H‐ZSM‐5 zeolite .…”
Section: Brønsted Acidity Of Zeolitesmentioning
confidence: 99%
“…It was also shown that the ion-paired hydronium clusters can expel water molecules to form zeolite BAS upon the decrease of the temperature. [46] In addition, the solvation effect and proton transport efficiency can be induced by dispersion interactions as exemplified by the combined NMR and DFT study of trimethylphosphine oxide (TMPO) adsorption in H-ZSM-5 zeolite. [47] The proton solvation equilibrium depends on the topology and composition of the zeolite lattice which provide different spatial confinement effects and different adsorption structures.…”
Section: Distribution Mobility and Property-activity Relationships mentioning
confidence: 99%